Basel III: main issues for GCC banks - Alsharif, Mohammad; Md Nassir, Annuar; Kamarudin, Fakarudin; M. A., Zariyawati (IJECM Pub UK, 2016)
The last global crisis caused banks to incur massive write downs of trillions of U.S dollars that had an adverse impact on the global economy. Thus, after the global financial crisis started in 2007, the G20 group called for a tighter regulatory supervision on the financial institutions and for a critical review of the Basel II accord. This led to the introduction of the Basel III accord in Dec 2010. Basel III represents the most stringent form of regulatory restrictions that have ever been introduced. This accord significantly increases capital adequacy requirements, and introduces new liquidity requirements and a minimum leverage ratio. These new requirements are expected to restrict banks' activities and as a result will affect banks' performance. However, although most recent studies are trying to discuss and estimate the impact of this new accord on banks and economies in developed countries, it is expected this accord will result in severe impacts on banks and economies of undeveloped countries as alternative financing channels to the banking industry are generally weak. Therefore, this paper will shed light on possible impacts of this new accord on GCC countries, which are developing countries that depend on oil production and are exposure to a high systematic risk due to oil prices fluctuation. The GCC banking industry is a dual banking system that contains conventional and Islamic banks and their banking industry is considered the largest in the Middle East region. The GCC Islamic finance industry accounts for the largest share of the global Islamic finance industry. Therefore, this paper will discuss the possible impacts of the new Basel accord on GCC Islamic and conventional banks. More, this paper will provide a historical background and the key elements of the three Basel regulations, and also, provide recent key features of GCC banking industry.